PENGARUH WISATA TAMAN ASRI TERHADAP PEREKONOMIAN MASYARAKAT YANG BERADA DI SEKITAR JALUR 8 JEMBATAN 3 KECAMATAN AIR SALEK KABUPATEN BANYUASIN - mega kusuma putri (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2019)
The problem in this study is '' Is there the Effect of Taman Asri Tourism on the Economyof Communities in the vicinity of Lane 8 Bridge 3 Air Salek District Banyuasin Regency? '' Thepurpose in this study is to analyze the Effect of Taman Asri Tourism on the Economy ofCommunities around the Path 8 Bridge 3 Air Salek District Banyuasin Regency. This researchmethod uses quantitative descriptive method. The population in this study is the community thatlives around the beautiful garden consisting of 129 families, the sampling technique uses clustersampling (Area Sampling). Data collection techniques in this study used a questionnaire with agutman scale. The analysis used in this study used the t-test. The results of this research thatthere is an influence of Asri park tourism on the economy of the community has a pretty goodinfluence. From the calculation, the tcount is 4,943 while the table is 1,734. Then it was statedthat there was an influence of beautiful garden tourism on the economy of the people who werearound Line 8 Bridge 3 Air Salek District, Banyuasin Regency.